2020
DOI: 10.36778/jesya.v3i2.161
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT.Kahatex

Abstract: The study aims to determine the effect of employee motivation on PT. Kahatex, the influence of employee work discipline at PT. Kahatex, as well as motivation and work discipline towards employees at PT. Kahatex. The data analysis method in this study uses the casual association method and uses a quantitative approach with quantitative data processing techniques with data processing techniques using multiple regression analysis. The data collection technique used was a questionnaire. Questionnaires distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
1
0
5
Order By: Relevance
“…The results demonstrated that work motivation has a favorable impact on the productivity of PT Syncrum Logistics employees. The findings of this study are consistent with those of Hasyim et al (2020), The Impact of Motivation and Work Discipline on Employee Performance at PT Kahatex. The findings demonstrated a substantial relationship between work motivation and work discipline variables, and employee performance.…”
Section: The Influence Of Motivation On Employee Performancesupporting
confidence: 90%
“…The results demonstrated that work motivation has a favorable impact on the productivity of PT Syncrum Logistics employees. The findings of this study are consistent with those of Hasyim et al (2020), The Impact of Motivation and Work Discipline on Employee Performance at PT Kahatex. The findings demonstrated a substantial relationship between work motivation and work discipline variables, and employee performance.…”
Section: The Influence Of Motivation On Employee Performancesupporting
confidence: 90%
“…Motivasi adalah bagaimana cara untuk memberikan dorongan kepada karyawannya, agar dapat bekerja secara maksimal (Rosmaini & Tanjung, 2019). Keinginan yang dimiliki individu dalam melakukan suatu kegiatan tertentu untuk mencapai suatu tujuan ialah suatu dorongan dari keadaan pribadi yang dikatakan sebagai motivasi yang dimiliki oleh individu (Hasyim et al, 2020). Motivasi mengarahkan kemampuan dan kekuatan karyawan untuk dapat berpartisipasi dengan produktif, sehingga mampu mewujudkan serta mencapai tujuan yang diterapkan (Mariati, 2018).…”
Section: Pendahuluanunclassified
“…Hal ini dikarenakan bahwa karyawan datang dan pulang tepat waktu yang sudah ditentukan sesuai aturan, bekerja dengan pakaian rapih, bertingkah laku sopan dan ramah, bekerja seusai dengan tugas yang diembannya, kemudian bertanggung jawab atas pekerjaannya, karyawan mengetahui aturan yang dibolehkan dan yang dilarang. Hasil penelitian ini sejalan dengan penelitian yang dilakukan oleh Shella, et al, (2019), dan Hasyim, et al, (2020), yang menyatakan bahwa disiplin kerja dapat mendorong peningkatan kinerja karyawan.…”
Section: Pengaruh Pelatihan Terhadap Kinerja Karyawan Pt Jasa Marga DI Gerbang Tol Cikampek Utamaunclassified
“…Jasa Marga di Gerbang Tol Cikampek Utama. Hasil penelitian ini sama dengan hasil penelitian yang dilakukan oleh Sari (2018), Efendy & Lesmana (2018), Shella, et al, (2019, dan Hasyim, et al, (2020), yang menyatakan bahwa pelatihan dan disiplin kerja dapat mendorong peningkatan kinerja karyawan.…”
Section: Variabelunclassified